Distribution and Characteristics of Halobates germanus Population in the Red Sea - Mahadik, Gauri A.; Agusti, Susana; Duarte, Carlos M. (Frontiers in Marine Science, 2019)
We investigated the occurrence of the sea skater Halobates spp. from samples collected at a fixed time series station and from six cruises along the north-south extend of the Red Sea during 2016-2018. Halobates germanus White, 1883 was the only species found during our study, its distribution ranging between 17° 9´ N - 27° 27´ N and between 35° 67´ E - 41° 49´ E. Total H. germanus abundance ranged between zero to 158,610 individuals km-2 with a considerable temporal (at the fixed station) and spatial (cruises) variation. In general, nymphs of different instar stages dominated the population, followed by females and males. The sex ratio was female-biased, with a higher number of females than males. Presence and prevalence of eggs, exuviae (moults) and early nymphal stages indicate a year round breeding cycle by H. germanus. The apparent optimum temperature for H. germanus occurrence in the central Red Sea was at 28.2°C, corresponding to peak abundances in spring and fall. Absence of any significant correlation of the abundances with environmental parameters indicate relative resilience of H. germanus to changes in environmental conditions.